2022
DOI: 10.1002/er.8023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cooling flow field of proton exchange membrane fuel cell based on heat transfer performance enhancement

Abstract: Proton exchange membrane fuel cell (PEMFC) generates a lot of heat during power generation. It is necessary to control PEMFC to operate at proper temperature through effective thermal management. CFD model of flow field plates with different structures is established; the heat transfer performance of different flow fields was analyzed by numerical simulation. The index of uniformity temperature (IUT) was introduced to further evaluate the heat transfer effect. The results showed that the parallel flow field wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Despite the significant advantages, the amount of electricity produced by a single PEMFC chemical reaction is not enough to meet the needs of commercial applications such as vehicles, and this disadvantage can be well eliminated by stacking them alternately and combining them in series to form a stack structure. The role of bipolar plates (BPP) in the stack structure is significant, and the flow field structure present inside them can induce the diffusion pattern of reactants in the channel of the stack gas [7][8][9]. Numerous studies in the literature have shown that hydrothermal management is a decisive factor for cell efficiency [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant advantages, the amount of electricity produced by a single PEMFC chemical reaction is not enough to meet the needs of commercial applications such as vehicles, and this disadvantage can be well eliminated by stacking them alternately and combining them in series to form a stack structure. The role of bipolar plates (BPP) in the stack structure is significant, and the flow field structure present inside them can induce the diffusion pattern of reactants in the channel of the stack gas [7][8][9]. Numerous studies in the literature have shown that hydrothermal management is a decisive factor for cell efficiency [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%